Efficacy and Safety of Lamivudine or Telbivudine in Preventing Mother-to-Child Transmission of Hepatitis B Virus: A Real-World Study - Li, Zhenhua (Biomed Res Int, 2020)
BACKGROUND: There are few large sample studies evaluating the safety and efficacy of lamivudine (LAM) or telbivudine (LdT) in preventing hepatitis B mother-to-child transmission (MTCT) in highly viremic mothers in the third trimester of pregnancy in real-world settings. The purpose of this study was to analyze a large sample size of HBV-infected mothers to better understand the safety and efficacy of LAM and LdT under the aforementioned criteria. METHODS: During the period of November 2008 to November 2017, we retrospectively enrolled mothers with HBV DNA > 1 × 10(6) IU/mL who received LAM or LdT during the third trimester of pregnancy and compared them to untreated mothers. All mothers were divided into the three following groups: the LAM group, the LdT group, and the control group. RESULTS: A total of 2624 HBV-infected mothers were enrolled in the study, with 363 in the LAM group, 1283 in the LdT group, and 978 in the control group. The MTCT rates were significantly lower in the LAM or LdT group than that in the control group (0.4% or 0.3% versus 9.0%, P < 0.001). Infants born to untreated mothers had a significantly higher risk of HBV infection (OR = 28.6, 95% CI: 10.4–78.7, P < 0.001). There were no significant differences in perinatal complications between the three groups (P > 0.05). There were also no differences for gestational age or infants' height, weight, Apgar scores, or birth defect rates. Postpartum discontinuation of antiviral therapy did not seem to increase the risk of postpartum alanine aminotransferase (ALT) flare. CONCLUSION: LAM or LdT treatment initiated in the third trimester for mothers with HBV DNA > 1 × 10(6) IU/mL was equally safe and effective in preventing MTCT.